TREATMENT OF WASTEWATER FROM SWINE AND POULTRY SLAUGHTERHOUSES - MIRELA SUCEVEANU (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2018)
The meat processing industry produces large volumes of slaughterhouse wastewater (SWW). For this reason, water and wastewater treatment has become crucial for the continuing development of the society. The present study reveals the water pollution degree from poultry and the swine slaughterhouses from Bacau (Romania). The possibility of reducing the quantity of pollutants by the active sludge treatment method is also presented. The efficiency of this treatment processes was evaluated through the following parameters: biochemical oxygen demand (BOD5), chemical oxygen demand (COD), total suspended solids (TSS), turbidity, both before and after the active sludge treatment.